Increasing Students' Critical Thinking Capacity: Bridging The Worlds Of Thought And Action - Banik, Lodia Amelia; Lelo, Kaleb; Nubatonis, Sonia M; Djami Manu, Kevin P; Seko, Sri N; Bili, Nadia F. M (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
It is important for students to understand their role in connecting thought and action, because this is an important foundation in achieving personal success. In response to this problem, the team of lecturers in the Philosophy of Science, Logic and Interpersonal Communication courses carried out PKM in the form of increasing the critical thinking capacity of students in the IAKN Kupang Pastoral Counseling and Christian Psychology Study Program through seminar activities with the theme "Bridging the Worlds of Thought and Action". The activity implementation method consists of several stages. These stages are planning, implementation and evaluation. The final results of this activity show that there is a significant impact obtained by students, especially on understanding thoughts and how to align participants' thoughts with actions in the real world, so that students are able to bridge the gap between creative thoughts and real actions in everyday life.